Low Intensity Operations: Subversion, Insurgency, Peace-Keeping. - Kitson, Frank (GHQ, Rawalpindi Army Educaiton Publishing House, 2006)
Low Intensity Operations is an important, controversial and prophetic book that has had a major influence on the conduct of modern warfare. First published in 1971, it was the result of an academic year Frank Kitson spent at University College, Oxford, under the auspices of the Ministry of Defence, to write a paper on the way in which the army should be prepared to deal with future insurgency and peacekeeping operations. Its findings and propositions are as striking as when the work was first published. "To understand the nature of revolutionary warfare, one cannot do better than read Low Intensity Operations...The author has had unrivalled experience of such operations in many parts of the world". (Daily Telegraph). "A highly practical analysis of subversion, insurgency and peacekeeping operations...Frank Kitson's book is not merely timely but important". (The Economist).
Includes Index and Bibliography.
Keywords: Guerrilla Warfare -- Subversive Activities -- Insurgency